Surveys of economic theory : Money Interest and Welfare Vol. 1 - American Economic Association; Royal Economic Society (Great Britain) (London ; New York : Macmillan ; St Martin's Press, 1965)
The book covers: The purpose of these surveys; Monetary Theory and Policy; A Survey of Inflation Theory; Recent Theories Concerning the Nature and Role of Interest; A Survey of Welfare Economics, 1939-59.
"First published in the American economic review and the Economic journal."
Includes bibliographical references.
rpm 05/07/2017
Loans
Keywords: Economics; Economics--Methodology